The "Melukat" Tradition As Millennial Religious Tourism In Badung, Bali - Putu Ratna Juwita Sari; Ni Nyoman Sri Wisudawati; Ni Made Dhian Rani Yulianti (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2022)
One of the religious tourisms known as melukat in Bali is a form of spiritual tourism that initially aims to gain peace of mind and draw closer to God Almighty. The increasing number of tourists who are interested in melukat lately is due to various other motivations such as getting recognition from others. Social media is one form of communication media used by the millennial generation to find information about the purpose of melukat which is currently viral. The aim of this study was to determine the motivation of the millennial generation to do this religious travelling and to find out whether the Fear of Missing Out (FoMO) phenomenon is one of the causes of the millennial generation to carry out this activity. The research method used in this research was qualitative. It was conducted using primary data and the data collection through observation and interviews with the local guide, tourists, and the priest at the location of melukat.The findings of the study indicate that the motivation for traveling by most of the millennial tourits is to follow the trend that is currently popular on their social media and their fear of not being able to match the community. Based on this phenomenon, it is essential to prepare an attractive and advantageous tourism